Politik Identitas Masyarakat Tengger dalam Mempertahankan Sistem Kebudayaan dari Hegemoni Islam dan Kekuasaan - Maksum, Ali (UIN Maulana Malik Ibrahim Malang, 2015)
This article explores the dynamic of Tengger communities life in order to defend its culture with regard to the expansion of Islam and the power of Indonesian government. The research were conducted in two villages, Ngadisari and Sapikerep, Probolinggo. Using the perspective of representation theory, this study elaborate more detail about the strategy of the Tengger people in representing their identity in the midst of the dynamics of the changing time. The dynamics dialectic between the Tengger and power (Islam) have brought out two important propositions. First, because of the strong tradition and culture Tengger systems, both Hindu and Islamic ideology interpreted as a cultural system that only symbolically attached to the Tengger. Second, although impressed syncretic, in fact, Islam and Hinduism also established world view Tengger substantive and culturally. The second view is as commonly as Islam in Java,